2021
DOI: 10.1371/journal.pone.0260737
|View full text |Cite
|
Sign up to set email alerts
|

Projection-based stereolithography for direct 3D printing of heterogeneous ultrasound phantoms

Abstract: Modern ultrasound (US) imaging is increasing its clinical impact, particularly with the introduction of US-based quantitative imaging biomarkers. Continued development and validation of such novel imaging approaches requires imaging phantoms that recapitulate the underlying anatomy and pathology of interest. However, current US phantom designs are generally too simplistic to emulate the structure and variability of the human body. Therefore, there is a need to create a platform that is capable of generating we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The exposure gradient through the layer and the double exposure of the top section of each layer results in a gradient cross-linking density across each printed layer. This exacerbates the gradient of cross-linking degree and adversely affects the mechanical properties across the thickness of the layer, which agrees with the results in Figure …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The exposure gradient through the layer and the double exposure of the top section of each layer results in a gradient cross-linking density across each printed layer. This exacerbates the gradient of cross-linking degree and adversely affects the mechanical properties across the thickness of the layer, which agrees with the results in Figure …”
Section: Discussionsupporting
confidence: 90%
“…This exacerbates the gradient of cross-linking degree and adversely affects the mechanical properties across the thickness of the layer, which agrees with the results in Figure 2. 24 In our previous study, we found that the monolithic sample, which did not contain the QY photoabsorber in its prepolymer solution, had the highest degree of cross-linking and highest E, as indicated by both 1 H NMR spectra and nanoindentation measurements. On the other hand, the multilayer sample, which had the highest concentration of QY photoabsorber, exhibited a lower degree of cross-linking as well as E. This observation suggests that a higher concentration of QY photoabsorber in the prepolymer solution leads to a reduction in the degree of cross-linking in the cross-linked hydrogel, as shown in Figures 2id,iid, and 3a,b.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…46,47 Any inhomogeneity or gradient in crosslinking within each layer is attributed to the absorption of the UV light by the photoabsorber in the prepolymer solution resulting in a spatial decay of light intensity during the crosslinking process. 48,49 There was no obvious change in the monolithic mono-1200 μm-3 s and mono-1200 μm-15 s in terms of their visual appearance, as there is no interlayer interface within the structure (Figure 4cii, right). High magnification cross-sectional SEM images of vacuum-dried multilayer PEGDA showed imperfections that appear as pockets of voids, both at interfaces and within printed layers.…”
Section: Resultsmentioning
confidence: 99%
“…Interface failure could be due to the residual stress at the interface between the top section of the previously printed layer and the bottom section of the newly formed layer. The top section is assumed to be sufficiently cross-linked as it is closer to the UV light, while the bottom section is farther away from the UV light and is assumed to be less cross-linked in comparison. , Any inhomogeneity or gradient in cross-linking within each layer is attributed to the absorption of the UV light by the photoabsorber in the prepolymer solution resulting in a spatial decay of light intensity during the cross-linking process. , There was no obvious change in the monolithic mono-1200 μm-3 s and mono-1200 μm-15 s in terms of their visual appearance, as there is no interlayer interface within the structure (Figure cii, right). High magnification cross-sectional SEM images of vacuum-dried multilayer PEGDA showed imperfections that appear as pockets of voids, both at interfaces and within printed layers .…”
Section: Resultsmentioning
confidence: 99%